Review—Electroreduction of peroxodisulfate: A review of a complicated reaction - Shafiee, Saiful 'Arifin; Aarons, Jolyon; Hamzah, Hairul Hisham (IOP Publishing, 2018)
The electroreduction of peroxodisulfate has been studied on various electrode materials for decades. However, the reduction of peroxodisulfate is not fully understood to date. Many research groups have searched for an electrode material that exhibits a diffusion-controlled response in the electroreduction of peroxodisulfate. However, the voltammetric responses obtained on most electrode materials have shown a kinetically-controlled reaction. Reaction mechanisms of peroxodisulfate reduction have also been proposed by a few groups. This review paper focuses on the electrochemical responses for the reduction of peroxodisulfate obtained on platinum, gold, platinized platinum, and bismuth-adsorbed platinum electrodes. This paper will not review the polarograms obtained on mercury drop electrodes for the reduction of peroxodisulfate anions because we believe that the results do not contribute to the understanding of the electrochemical reactions. We propose a simplified version of the reaction mechanisms. This paper also reviews the kinetic models proposed by several groups which could assist the readers to apprehend the kinetic behaviors of peroxodisulfate reduction. This paper discusses several issues related to peroxodisulfate from the natural decomposition of peroxodisulfate to the reaction mechanisms of peroxodisulfate reduction